812 Mortality Risk prediction in Emergency Laparotomy (ORIEL) Study Outcomes at Wythenshawe Hospital. (12th October 2021) - Carey, C; Pittam, B; Mobarak, S; Varley, R; Kingston, J; Agwunobi, A
Abstract: Aim: Emergency laparotomy is a high-risk procedure with significant morbidity and mortality. ORIEL is a multi-centre national study aiming to compare the 30-day mortality predictions generated by NELA, P-POSSUM, ACS-NSQIP and SORT risk calculators with observed 30-day mortality rates in patients undergoing emergency laparotomies. We present the data collected from Wythenshawe hospital. Method: Data were collected retrospectively on adult patients undergoing an emergency laparotomy between 01/12/2017 to 30/11/2019 at Wythenshawe hospital from the online NELA database. The median pre-operative mortality risks were calculated using the four risk calculators for all patients. Mortality and morbidity were compared with data reported in the Sixth NELA report. Results: The median predicted pre-operative mortality (IQR) for all patients studied using NELA, P-POSSUM, ACS-NSQIP and SORT were: 4.3 (13.0), 5.2 (14.2), 3.4 (8.2) and 2.9 (9.3) respectively. Among patients who were alive 30 days post-operatively, the median predicted mortalities (IQR) were: 3.8 (8.5), 4.8 (11.0), 2.6 (6.9) and 2.8 (7.1) respectively, and among those who died were: 30.8 (18.9), 30.3 (63.4), 16.9 (13.9) and 20.3 (16.2). Compared to the national average, mortality rates at Wythenshawe were lower (9% v 9.3%), the median length of stay in hospital was lower (12 days v 15.4 days) and the percentage of high-risk patients admitted to critical care was higher (93% v 85%). Conclusions: Similar values were generated with all the scoring systems among all patients. Wythenshawe hospital reports lower mortality rates and shorter stays in hospital despite operating on higher risk patients (ASA grades 3-5).